2021
DOI: 10.4103/2221-1691.310204
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and senescence modulatory effects of rice bran extract on 4T1 and NIH-3T3 cells co-treatment with doxorubicin

Abstract: Objective: To determine the effect of rice bran extract (RBE) in combination with doxorubicin on 4T1 triple-negative breast cancer cells and NIH-3T3 cells. Methods: RBE was obtained by maceration with n-hexane. The phytochemical profile of RBE was observed using highperformance liquid chromatography. Cytotoxic effect of RBE was evaluated through MTT assay. In addition, flow cytometry was used for cell cycle and apoptosis analysis. Cellular senescence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In this study, HST demonstrated its ability to increase the efficacy of PGV-1 and could help to protect surrounding cells from damage. In general, cell damage can be induced by oxidative agents including drugs, cellular stress, and poisons (Madkour 2020;Zulfin et al 2021). These findings provide backing for the prospective development of HST as a co-chemotherapeutic agent, capable of enhancing the cytotoxic impact of chemotherapy agents and to reduce the cellular damages caused by toxic agents, including oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, HST demonstrated its ability to increase the efficacy of PGV-1 and could help to protect surrounding cells from damage. In general, cell damage can be induced by oxidative agents including drugs, cellular stress, and poisons (Madkour 2020;Zulfin et al 2021). These findings provide backing for the prospective development of HST as a co-chemotherapeutic agent, capable of enhancing the cytotoxic impact of chemotherapy agents and to reduce the cellular damages caused by toxic agents, including oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…( 16) Senescence is a cellular event occurring naturally as a sign of abnormal ROS level of the cell, leading to apoptosis of the cell. (17,18) This can be one approach for killing cancer cells, including TNBC. On the other hand, it has been mentioned before that TNBC has the lowest prognosis among the different subtypes of cancer.…”
Section: Introductionmentioning
confidence: 99%